Characterization of the inflammatory proteome of synovial fluid from patients with psoriatic arthritis: Potential treatment targets - Barbarroja, Nuria; López-Montilla, Maria Dolores; Cuesta-López, Laura; Pérez-Sánchez, Carlos; Ruiz-Ponce, Miriam; López-Medina, Clementina; Ladehesa-Pineda, Maria Lourdes; López-Pedrera, Chary; Escudero-Contreras, Alejandro; Collantes-Estévez, Eduardo; Arias-de la Rosa, Iván (Frontiers in Immunology, 2023)
Objectives: 1) To characterize the inflammatory proteome of synovial fluid (SF) from patients with Psoriatic Arthritis (PsA) using a high-quality throughput proteomic platform, and 2) to evaluate its potential to stratify patients according to clinical features. Methods: Inflammatory proteome profile of SF from thirteen PsA patients with active knee arthritis were analysed using proximity extension assay (PEA) technology (Olink Target 96 Inflammation panel). Four patients with OA were included as control group. Results: Seventy-nine inflammation-related proteins were detected in SF from PsA patients (SF-PsA). Unsupervised analyses of the molecular proteome profile in SF-PsA identified two specific phenotypes characterized by higher or lower levels of inflammation-related proteins. Clinically, SF-PsA with higher levels of inflammatory proteins also showed increased systemic inflammation and altered glucose and lipid metabolisms. Besides, SF from PsA patients showed 39 out of 79 proteins significantly altered compared to SF-OA specifically related to cell migration and inflammatory response. Among these, molecules such as TNF, IL-17A, IL-6, IL-10, IL-8, ENRAGE, CCL20, TNFSF-14, OSM, IFN, MCP-3, CXCL-11, MCP4, CASP-8, CXCL-6, CD-6, ADA, CXCL-10, TNF and IL-7 showed the most significantly change. Conclusion: This is the first study that characterizes the inflammatory landscape of synovial fluid of PsA patients by analyzing a panel of 92 inflammatory proteins using PEA technology. Novel SF proteins have been described as potential pathogenic molecules involved in the pathogenesis of PsA. Despite the flare, inflammatory proteome could distinguish two different phenotypes related to systemic inflammation and lipid and glucose alterations.